2014
DOI: 10.1039/c4ce01730g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high pressure on the crystal structure and charge transport properties of the (2-fluoro-3-pyridyl)(4-iodophenyl)borinic 8-oxyquinolinate complex

Abstract: The crystal and molecular structure of IJ2-fluoro-3-pyridyl)IJ4-iodophenyl)borinic 8-oxyquinolinate has been determined at room temperature at pressures ranging from ambient to 4.9 GPa in approximately 1 GPa steps. The crystal structure symmetry is conserved during the compression while the a, b and c unit cell dimensions were compressed by 7.5%, 8.0% and 6.9%, respectively. The crystal cell volume decreased by 19.4%. The analysis of the compression of the crystal was supported by computational results obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 75 publications
(135 reference statements)
0
10
0
Order By: Relevance
“…According to the obtained XRD data (this work) and our processing of the CSD, such σ-donors as isocyanides and the IAd carbene under normal conditions form the shortest I•••C contacts (<3.1 Å) in the crystal state. The other C-based XB acceptors like carbon-involved π-systems also provide short XBs (d XB = 3.07-3.20 Å), but mostly under high external pressure (1.9 and 3.96 GPa) 33,34 . To the best of our knowledge, XBs with other types of C-based σ-donors (e.g., CO or C-ylides), acting as XB acceptors, have never been detected.…”
Section: Solution and Mechanochemical Routes To Isocyanide Adductsmentioning
confidence: 99%
“…According to the obtained XRD data (this work) and our processing of the CSD, such σ-donors as isocyanides and the IAd carbene under normal conditions form the shortest I•••C contacts (<3.1 Å) in the crystal state. The other C-based XB acceptors like carbon-involved π-systems also provide short XBs (d XB = 3.07-3.20 Å), but mostly under high external pressure (1.9 and 3.96 GPa) 33,34 . To the best of our knowledge, XBs with other types of C-based σ-donors (e.g., CO or C-ylides), acting as XB acceptors, have never been detected.…”
Section: Solution and Mechanochemical Routes To Isocyanide Adductsmentioning
confidence: 99%
“…11 The optical properties of such complexes can be tuned mainly through the appropriate choice of a ligand acting as a chromophore. 17,18 There is a wide variety of available structures, but among them borinic complexes with (O,N)-chelating ligands have been extensively studied, presumably due to their relatively high (in most cases) stability. 2,[12][13][14][15][16] Moreover, we have proved that different crystal packing induced by either compression in diamond anvil cells or crystallization of different polymorphs can be used to improve charge transport properties (which is very important from the standpoint of application in light emitting devices).…”
Section: Introductionmentioning
confidence: 99%
“…1), represent their close analogues as they also possess phenolate oxygen and imine nitrogen atoms coordinated to the central B atom by means of covalent and dative bonds, respectively. 2,17,18,26 We observed that the character of aryl groups attached to the boron centre can influence the optical (quantum yield of emission) and other physicochemical (e.g., charge transport) properties. In general, the synthesis of salicylaldimine chelating ligands is simple and efficient.…”
Section: Introductionmentioning
confidence: 99%
“…as temperature, can have an impact upon the geometric parameters defining weak, intermolecular interactions. 244,245 In this context and the above notwithstanding, it is worth mentioning a room temperature, variable-pressure study 246 of previously described 19, 88…”
Section: Crystengcomm Accepted Manuscriptmentioning
confidence: 90%